[tex]2\frac{2}{29} *(\frac{3}{5}-\frac{5}{18} )-15:5\frac{5}{8} = \frac{60}{29} *(\frac{18*3-5*5}{90} )-15*\frac{8}{45} =\frac{60}{29} *\frac{29}{90} -\frac{15*8}{45} =\frac{60*29}{29*90} -\frac{8}{3} =\frac{2}{3} -\frac{8}{3} =-\frac{6}{3} =-2[/tex]
Ответ: −2.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]2\frac{2}{29} *(\frac{3}{5}-\frac{5}{18} )-15:5\frac{5}{8} = \frac{60}{29} *(\frac{18*3-5*5}{90} )-15*\frac{8}{45} =\frac{60}{29} *\frac{29}{90} -\frac{15*8}{45} =\frac{60*29}{29*90} -\frac{8}{3} =\frac{2}{3} -\frac{8}{3} =-\frac{6}{3} =-2[/tex]
Ответ: −2.